Equivalent linear algebraic expressions

## Not equivalent expressions

If the two expressions were not equal for a value of t then they would **not** be equivalent.

For example, 2 − 3t is **not** equivalent to 3t − 2.

Let t = 1,

then 2 − 3t = 2 − 3 = −1

and 3t − 2 = 1

2 − 3t is not equal to 3t − 2 when t = 1.

But if t = \(\dfrac{2}{3}\)

then 2 − 3t = 0

and 3t − 2 = 0. (Try this.)

So the expression 2 − 3t is not equivalent to the expression 3t − 2 because they are not equal for all values.

© Australian Mathematical Sciences Institute, except where indicated otherwise. This material is licensed under a Creative Commons Attribution-NonCommercial 3.0 Unported (CC BY-NC 3.0) licence http://creativecommons.org/licenses/by-nc/3.0/